Literatur Review Pengaruh Employee Engagement dan Kepuasan Kerja Terhadap Kinerja Organisasi Di Era Digital - Lailatus Sa’adah; Nur Afnenda Apriliya Rahayu; Musliana Fatikaningrum; Muhammad Sheva Fathoni (Universitas Ratu Samban, 2026)
This study aims to analyze the influence of employee engagement and job satisfaction on organizational performance in the digital era. Digital transformation has changed the working environment and requires organizations to manage human resources adaptively in order to maintain optimal performance. This research employed a systematic literature review method by examining relevant national and international academic articles published between 2015 and 2025. The literature was collected from various scientific databases, selected based on inclusion and exclusion criteria, and analyzed using narrative and thematic synthesis. The results indicate that employee engagement and job satisfaction have a positive and significant effect on organizational performance. Employees with higher levels of engagement and job satisfaction tend to demonstrate better productivity, commitment, and adaptability to technological changes. Furthermore, a digital work environment can strengthen the relationship between engagement, job satisfaction, and organizational performance when supported by appropriate systems and organizational culture. This study provides important implications for organizations in developing effective human resource management strategies in the digital era..